IMPLEMENTATION OF PROBLEM SOLVING APPROACH CAN IMPROVE ENGLISH THE LEARNING OUTCOMES AT CLASS IV SD NEGERI 7 KUTAMAKMUR KABUPATEN ACEH UTARA - Nuraini, Nuraini (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
This research is class action research (Classroom Action Research) which consists of two cycles, each cycle is held in three meetings. This research was conducted in 2022. The research procedures included planning, implementing actions, observing, and reflecting. The subjects in this study were students of Class IV SD Negeri 7 Kutamakmur Kabupaten Aceh Utara.Â Based on the results of the analysis of the data obtained in this study, it can be concluded as follows: Learning using a problem solving approach can improve learning outcomes for class IV SD Negeri 7 Kutamakmur Kabupaten Aceh Utara . This is indicated by the increase in the completeness of student learning outcomes at Class IV SD Negeri 7 Kutamakmur Kabupaten Aceh Utara. Â Of the 13 students (61.90%) who were in the complete category in cycle I increased to 19 students (90.50%) in cycle II. The application of the problem-solving approach in learning can increase student activity, this can be seen from the observation sheet of student activity in the positive response of students in learning.